Kajian Teknik Budidaya Kelapa Sawit (Elaeis guineensis Jacq.) Pada Sistem Budidaya Petani Lokal Di Desa Bawofanayama, Kabupaten Nias Selatan - Lilis Sartika Gulo; Berliana Vivi Lestari Lase; Awal Sepkurniawan Waruwu; Yupika Ananda Mendrofa; Dian Agung Sanora Laia (Universitas Khairun, 2026)
Oil palm (Elaeis guineensis Jacq.) is one of the leading plantation commodities that makes a significant contribution to the local economy, including in South Nias Regency. This paper was prepared to conduct a descriptive analysis of the oil palm cultivation techniques applied by local farmers at the Kilometer 7 Plantation in Bawofanayama Village, Fanayama Subdistrict, and to assess their compliance with the principles of Good Agricultural Practices (GAP) as stipulated in Ministry of Agriculture Regulation No. 131/Permentan/OT. 140/12/2013. The study was conducted using a qualitative descriptive approach, employing participatory observation, in-depth interviews with farmers, and field documentation during the Integrated Field Study program. The results of the study show that farmers apply a number of technical practices characteristic of smallholder plantations, including planting using a soil mound system without planting holes, an equilateral triangle planting pattern spaced 9 × 9 meters apart, fertilization using the drip irrigation technique, the use of pruned palm fronds as mulch, the use of swiftlet droppings and coconut shell charcoal as soil conditioners, and natural pest control using a saltwater solution. Although most cultivation stages were in line with technical recommendations, challenges were also identified, such as suboptimal drainage systems, inconsistent frond pruning, and labor constraints because plantation management still relies primarily on family labor. This study is expected to serve as a reference for the development of more productive and sustainable smallholder oil palm cultivation, particularly in the South Nias region, where scientific research on this topic has been limited to date.